Sago pulp and rice husk as an alternative material for the cultivation of oyster mushroom (Pleurotus ostreatus). Issue 1 (April 2020) - Taskirawati, I; Rosdiana,; Baharuddin,
Abstract: During this time, the wood powder is one of the primary raw materials in making mushroom cultivation media. Alternative other raw materials need to be developed to diversify the oyster mushroom cultivation media. Sago pulp waste and rice husk are chosen as the planting medium for oyster mushroom cultivation because they contain cellulose, hemicellulose, and lignin needed by the fungus. This study aims to determine the composition of sago pulp and rice husk as the best growing media for the growth and development of white oyster mushrooms. The method used in this study is mixing raw materials (the cultivation media), sterilizing raw materials, inoculating, maintaining, and harvesting. There are five treatments in mixing raw materials, namely the use of 100% sago pulp waste (P1); 75% of sago pulp and 25% of husk rice powder (P2); 50% of sago pulp and 50% of husk rice powder (P3); 25% sago waste and 75% husk rice powder (P4); and 100% rice husk (P5) as a control. The use of 50% sago pulp and 50% husk rice powder (P3) and 25% sago pulp and 75% husk rice powder (P4) produces the right cultivation media. Whereby using both of these mediums, it takes 42 days from the growing media inoculated mushrooms until the oyster mushrooms are ready to be harvested. However, if the use of baglog P3 as a growth medium will get better yields because of the wet weight (60 grams) and the number of mushroom fruit bodies (16 fruits) that harvested is higher.